The development and standardization of a group screening audiometer and procedure for Indian condition - Kalai Selvan MG (Journal of All India Institute of Speech and Hearing, 1979)
Auditory screening is an attempt to identify persons who have significant hearing defects from a population made up predominently of people with normal or adequate hearing. Thetechnique of screening is as it is purpose the identification as quickly as economically as possible and individuals in a large population who are in need of some special service